2016
DOI: 10.3102/0034654315626799
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effects of Classroom Management Strategies and Classroom Management Programs on Students’ Academic, Behavioral, Emotional, and Motivational Outcomes

Abstract: A meta-analysis of the effects of classroom management strategies and classroom management programs on students' academic, behavioral, emotional, and motivational outcomes Korpershoek, Hanke; Harms, Truus; de Boer, Hester; van Kuijk, Mechteld; Doolaard, Simone Link to publication in University of Groningen/UMCG research database Citation for published version (APA): Korpershoek, H., Harms, T., de Boer, H., van Kuijk, M., & Doolaard, S. (2016). A meta-analysis of the effects of classroom management strategies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
294
2
18

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(392 citation statements)
references
References 82 publications
8
294
2
18
Order By: Relevance
“…Being a relatively brief study there may have been insufficient time available to develop prosocial behavior that require student-motivated change regarding personal values and involvement in forms of social skills training (Bandy & Moore, 2011;Kidron & Fleishman, 2006;Lochman, Coie, Underwood, & Robert, 1993). The results found in this study are similar to other studies which use formalized training programs to increase the teacher's knowledge and ability to manage classes in an effective manner (Piwowar, Thiel, & Ophardt, 2013;Korpershoek, Harms, de Boer, van Kuijk, & Doolaard, 2016). Even brief programs for teachers that focused on managing the overall classroom environment have had an impact on reducing problematic behavior with more disruptive students (Snyder et al, 2011).…”
Section: Conclusion and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Being a relatively brief study there may have been insufficient time available to develop prosocial behavior that require student-motivated change regarding personal values and involvement in forms of social skills training (Bandy & Moore, 2011;Kidron & Fleishman, 2006;Lochman, Coie, Underwood, & Robert, 1993). The results found in this study are similar to other studies which use formalized training programs to increase the teacher's knowledge and ability to manage classes in an effective manner (Piwowar, Thiel, & Ophardt, 2013;Korpershoek, Harms, de Boer, van Kuijk, & Doolaard, 2016). Even brief programs for teachers that focused on managing the overall classroom environment have had an impact on reducing problematic behavior with more disruptive students (Snyder et al, 2011).…”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…The implications of understanding teacher's ability to manage their classrooms is important, given that within Asian countries, the ability to management classroom behaviours is perceived as an important marker of competency amongst new teachers (Goh, 2013), and is thus a topic that needs to be taken seriously in order to support the developing professional identify of new teachers. Furthermore, encouraging teacher education programs that focus on classroom management is important given the flow-on effects from improved student behavior, and associated variables such as improved academic performance (Korpershoek et al, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…En este sentido los hallazgos de otros estudios han demostraron que la educación emocional impacta positivamente en el bienestar infantil, debido a que incrementan la comprensión y la regulación de emociones, reducen los síntomas emocionales y fortalecen un concepto del yo saludable, además de promover la autogestión efectiva (Ambrona, López-Pérez, & Márquez-González, 2012;Morgan, Izard, & Hyde, 2014;Slee et al, 2009). De igual forma, se encontró que trabajar sobre las dimensiones emocionales promueve las competencias socioemocionales, llevando a una reducción de síntomas externalizados tal como la conducta agresiva, problemas conductuales y la hiperactividad, y, al mismo tiempo, promueve las habilidades sociales, la conducta prosocial y el cumplimiento de las reglas del contexto (Ambrona et al, 2012;Korpershoek, Harms, de Boer, Van Kuijk, & Doolaard, 2016;Moraru, Stoica, Tomuletiu, & Filpisan, 2011;Morgan et al, 2014;Slee et al, 2009). Asimismo, el fortalecimiento de las capacidades de regulación emocional se asocia con mejor salud física (Berking & Wupperman, 2012;Galdona, Urdaneta, Aldaz, Laskibar, & Yanguas, 2011;Mathews, Kerns, & Ciesla, 2014), tanto como con una mayor preparación académica (Brophy-Herb, Zajicek-Farber, Bocknek, McKelvey, & Stansbury, 2013;Korpershoek et al, 2016;Moraru et al, 2011).…”
Section: Conclusionesunclassified
“…Effective classroom management practices promote appropriate behavior, and increase academic engagement, and, subsequently, academic achievement (Evertson & Weinstein, ; Garwood & Vernon‐Feagans, ; Korpershoek, Harms, de Boer, van Kuijk, & Doolaard, ; Stronge, Ward, & Grant, ). Research has identified a number of classroom management skills that teachers can easily implement in their classrooms, including increased active supervision, increased opportunities‐to‐respond (OTR), and behavior‐specific praise (BSP) (Conroy, Alter, & Sutherland, ; Simonsen, Fairbanks, Briesch, Myers, & Sugai, ; U.S. Department of Education, ).…”
mentioning
confidence: 99%